Role Model and Family Support Related to Self Efficacy Sleep in The Sand in Coastal Elderly - Hidayat, Syaifurrahman; Hannan, Mujib (South East Asia Nursing Research, 2021)
The elderly naturally experience a decrease in physical and psychological function so that it affects individuals in their daily activities. Self-efficacy is the ability to carry out a series of actions to provide life satisfaction for the elderly who sleep in the sand. Role models can provide role models for the elderly in doing activities to sleep in the sand where family support can influence the behavior of the elderly sleeping in the sand in the coastal elderly. The research method is descriptive-analytic with a cross-sectional approach. The population of this study were all the elderly who lived in the village, Village, Pasir Lenggung Batang Batang -District, Sumenep Regency as many as 124 elderly. The sampling technique used is purposive sampling. The analysis used is the test Spearman rank. The results of this study stated that most of the respondents had role models in the high category as many as 57.5% coastal elderly, respondents had family support in the medium category as many as 72.5% coastal elderly, and respondents had self-efficacy sleeping in the sand in the capable category as many as 72, 5% of coastal elderly. There is a relationship between the role model and the self-efficacy of sleeping in the sand in the coastal elderly and there is a relationship between family support and the self-efficacy of sleeping in the sand in the coastal elderly. Role models can be role models and motivations for the coastal elderly to sleep in the sand. When the role model is good, self-efficacy will increase, with that the ability of the elderly to carry out activities in the sand is better as well as the higher family support, the higher self-efficacy the elderly